Patterns of ovarian morphology in polycystic ovary syndrome: a study utilising magnetic resonance imaging. - Barber, T; Alvey, C; Greenslade, T; Gooding, M; Barber, D; Smith, R; Marland, A; Wass, J; Child, T; McCarthy, M; Franks, S; Golding, S (2010)
OBJECTIVE: To evaluate and compare MRI-based ovarian morphology in groups of women with polycystic ovary syndrome (PCOS) and controls. METHODS: All PCOS cases (n = 44) had oligo-amenorrhoea and hyperandrogenism irrespective of ovarian morphology, and fulfilled NIH/Rotterdam diagnostic criteria for PCOS. All control women (n = 40) had normal menses and normoandrogenaemia. All subjects were of white British/Irish origin and pre-menopausal. Group comparisons were based on independent-sample t tests. Polycystic ovarian morphology was defined by at least 12 follicles 2-9 mm in diameter and/or an ovarian volume greater than 10 cm(3). RESULTS: Ovarian morphology differed significantly in PCOS cases and controls (follicle number geometric mean [SD range] 18.6 [9.9, 35.0] vs 6.6 [3.1, 14.2], unadjusted P = 1.3 x 10(-16); calculated ovarian volume 8.8 cm(3) [5.0, 15.5] vs 5.1 cm(3) [2.5, 10.3], unadjusted P = 3.0 x 10(-7); peripheral follicle location in 55% vs 18% of ovaries, P = 7.9 x 10(-6); visible central ovarian stroma in 61% vs 24% of ovaries, P = 2.3 x 10(-5)). Follicle number and calculated ovarian volume were not concordant with clinical/biochemical assignment of PCOS/control status in 36 (23%) and 52 (34%) of ovaries, respectively. CONCLUSION: Ovarian morphology overlaps in PCOS cases and controls, emphasising the importance of considering clinical/biochemical presentation together with imaging ovarian morphology in the diagnosis of PCOS.